ANALISA FAKTOR YANG BERPENGARUH TERHADAP USIA KAWIN/NIKAH PERTAMA PEREMPUAN DI KABUPATEN WONOSOBO - Muhamad Sahli; Farikhah Indriani (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Purpose: This research purpose is to analyze the ef ect factors of wonosobo first marriagewomen. Methods: Type of research is quantitative. And samples are 95 respondents from 1902populations. Description analytic research using retrospective control and data analysis usingmultiple linear regrssion. Results: The results showed the influence of the education of respondents with p-value 0,011and influence secondary education with p-value 0,088. Patriach job ef ect are 0.030 p-valueRecommended: It is recomended to implement the compulsory education of 12 years that couldadd in high school with 3 km distances. Counseling of reproduction health could started inprimary schoolPurpose: This research purpose is to analyze the ef ect factors of wonosobo first marriagewomen. Methods: Type of research is quantitative. And samples are 95 respondents from 1902populations. Description analytic research using retrospective control and data analysis usingmultiple linear regrssion. Results: The results showed the influence of the education of respondents with p-value 0,011and influence secondary education with p-value 0,088. Patriach job ef ect are 0.030 p-valueRecommended: It is recomended to implement the compulsory education of 12 years that couldadd in high school with 3 km distances. Counseling of reproduction health could started inprimary schoolPurpose: This research purpose is to analyze the ef ect factors of wonosobo first marriagewomen. Methods: Type of research is quantitative. And samples are 95 respondents from 1902populations. Description analytic research using retrospective control and data analysis usingmultiple linear regrssion. Results: The results showed the influence of the education of respondents with p-value 0,011and influence secondary education with p-value 0,088. Patriach job ef ect are 0.030 p-valueRecommended: It is recomended to implement the compulsory education of 12 years that couldadd in high school with 3 km distances. Counseling of reproduction health could started inprimary schoolPurpose: This research purpose is to analyze the ef ect factors of wonosobo first marriagewomen. Methods: Type of research is quantitative. And samples are 95 respondents from 1902populations. Description analytic research using retrospective control and data analysis usingmultiple linear regrssion. Results: The results showed the influence of the education of respondents with p-value 0,011and influence secondary education with p-value 0,088. Patriach job ef ect are 0.030 p-valueRecommended: It is recomended to implement the compulsory education of 12 years that couldadd in high school with 3 km distances. Counseling of reproduction health could started inprimary school